(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The distribution system is to deliver water to consumer with appropriate quality and quantity. Pressure distribution system is used to collectively describe the facilities used to supply water from its source to the point of use. This paper refers to rural water supply and the distribution of the Mawada Pimpri village from the Nazare dam, located in the village of Nazaré, Purandar, Pune.Our research will minimize the cost of the water and water distribution system In addition to this project we provide water purification system in the distribution network, while the most economical water distribution system has been developed.